Modification of the existing maximum residue level for mandipropamid in radish leaves - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Luis Carrasco Cabrera; Irene Castellan; Monica delAguila; Lucien Ferreira; German Giner Santonja; Luna Greco; Samira Jarrah; Renata Leuschner; Javier Martinez Perez; et al. (EFSA Journal, 2023)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Syngenta Crop Protection AG submitted a request to the competent national authority in the Netherlands to modify the existing maximum residue level (MRL) for the active substance mandipropamid in radish leaves (classified under the subgroup of kales), based on an intended indoor use on radishes. The residue data in radish leaves submitted in support of the request were found to be sufficient to derive an MRL proposal for this commodity. Adequate analytical methods for enforcement are available to control the residues of mandipropamid on the commodity under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that long‐term intake of residues resulting from the use of mandipropamid according to the reported agricultural practice is unlikely to present a risk to consumer health. The reliable end points, appropriate for use in regulatory risk assessment are presented.